2018
DOI: 10.1177/0956797618783714
|View full text |Cite
|
Sign up to set email alerts
|

The Liking Gap in Conversations: Do People Like Us More Than We Think?

Abstract: Having conversations with new people is an important and rewarding part of social life. Yet conversations can also be intimidating and anxiety provoking, and this makes people wonder and worry about what their conversation partners really think of them. Are people accurate in their estimates? We found that following interactions, people systematically underestimated how much their conversation partners liked them and enjoyed their company, an illusion we call the liking gap. We observed the liking gap as stran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
97
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 42 publications
8
97
0
1
Order By: Relevance
“…At the same time, it proved that the negative deviation effect was not just caused by people's ownnegative thoughts of conversational performance, because the effect still existed in people who were not self-critique. Therefore, it is not entirely sufficient for Boothby (2018) to conclude that the more people thought negatively in the communication, the bigger the liking gap existed between them. While we found that the bigger or smaller gap still exists when people had no negative thoughts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At the same time, it proved that the negative deviation effect was not just caused by people's ownnegative thoughts of conversational performance, because the effect still existed in people who were not self-critique. Therefore, it is not entirely sufficient for Boothby (2018) to conclude that the more people thought negatively in the communication, the bigger the liking gap existed between them. While we found that the bigger or smaller gap still exists when people had no negative thoughts.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, why does the negative deviation effect exist? Is it appropriate to attribute this effect to the hypothesis that people are too focused on their negative thoughts of themselves to notice the signals of their mutual liking, as described in research previously 48 ? If there are no negative thoughts in the interpersonal communication, will there still be a negative deviation effect?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Boothby et al propose this is a universal illusion, which they label the 'liking gap'. 7 They observed new acquaintances among first-year college students, members of the public, and a laboratory team, and the findings were consistent: people systematically underestimate how much others like them and how much their company was actually enjoyed. It persisted across conversations of varying length, and could last months.…”
mentioning
confidence: 85%